Performance Evaluation of Different Doses of Triafamone 200 SC on Weed Dynamics of Transplanted Kharif Rice in Agroclimatic Zone of Andhra Pradesh, India - B. Jyothi Basu; P. Swathi; N. Sambasiva Rao; V. Saida Naik; T. Girwani (Archives of Current Research International, 2025)
Background: Weed management plays a pivotal role in Rice cultivation, particularly in transplanted Rice systems, where unchecked weed growth can lead to significant yield losses and reduced crop quality. Transplant Rice fields tend to face rampant weed transplant Rice fields tend to face rampant weed infestations because weeds experience highly conducive growth conditions, which results in a fierce competition for limited resources like nutrients, water, and sunlight. To counter this problem, chemical herbicides have proved to be one of the most effective measures for weed control against various weed species and maximizing crop productivity. Of the variety of herbicides on the market, Triafamone 200 SC is a potential candidate because it specifically targets a broad array of weeds and is also selective to Rice. The efficacy of Triafamone 200 SC compared to other herbicides is still an area of research. It is important to understand the comparative efficacy of various herbicides to formulate effective weed management plans specific to the agronomic situation. Methodology: A two-year field study was carried out during the 2017-18, Rabi season and the 2018-19, Kharif season at the Agricultural Research Station located at Jangamaheswarapuram, Guntur District, Andhra Pradesh, India. The experimental design comprised 13 treatments arranged in a completely randomized block structure with four replications. Weed control efficiency (WCE) indicates percent reduction in weed dry matter due to weed control treatments over unweeded control. The data on weeds were transformed by square root transformation by adding one before being subjected to ANOVA. Results: Findings from the study revealed that among the various treatments, Triafamone 200 SC @ 100 g a.i. ha⁻¹ applied at 2-3 days after transplanting (DAT) (T10) achieved the highest weed control efficiency, recording 68.64% during Rabi, 2017-18 and 60.83% in Kharif, 2018-19. This result was statistically comparable to the treatment T5 (Triafamone 200 SC @ 100 g a.i. ha⁻¹ applied at the 2-3 leaf stage of weeds), which achieved 63.60% and 59.02% efficiency in the respective seasons, while outperforming all other treatments in both years of the study. Conclusion: The applied weed management practices demonstrated significant effectiveness in controlling grasses, broad-leaved weeds and sedges, thereby reducing competition for essential growth resources.